2017
DOI: 10.1128/jvi.00184-17
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Induced Internalization of the Human Respiratory Syncytial Virus Fusion Protein

Abstract: Respiratory syncytial virus (RSV) infections remain a major cause of respiratory disease and hospitalizations among infants. Infection recurs frequently and establishes a weak and short-lived immunity. To date, RSV immunoprophylaxis and vaccine research is mainly focused on the RSV fusion (F) protein, but a vaccine remains elusive. The RSV F protein is a highly conserved surface glycoprotein and is the main target of neutralizing antibodies induced by natural infection. Here, we analyzed an internalization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
(90 reference statements)
0
12
1
Order By: Relevance
“…Primary CD4 ϩ T cells were infected with NL4.3 ADA green fluorescent protein (GFP) or CH58 T/F and dynamin was inhibited with the dynamin inhibitory peptide (DIP). This peptide blocks the binding of dynamin to amphiphysin and has been shown to reduce endocytic events (27,45,46). The addition of DIP significantly reduced bNAb-induced Env internalization in infected cells as measured by flow cytometry (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Primary CD4 ϩ T cells were infected with NL4.3 ADA green fluorescent protein (GFP) or CH58 T/F and dynamin was inhibited with the dynamin inhibitory peptide (DIP). This peptide blocks the binding of dynamin to amphiphysin and has been shown to reduce endocytic events (27,45,46). The addition of DIP significantly reduced bNAb-induced Env internalization in infected cells as measured by flow cytometry (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…It has been previously suggested that Ab-mediated cross-linking facilitates internalization of RSV fusion proteins. In this study, RSV Env endocytosis was significantly reduced when Fab fragments were used instead of their full MAb counterpart (27). To verify whether this was the case for HIV-1 Env, we performed side-by-side comparisons on the ability of full-length Abs versus their Fab fragments to reduce Env levels at the cell surface upon incubation at 37°C, as measured by flow cytometry.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…More importantly, the encephalitis patients’ CSF reduced the amplitude and frequency of miniature EPSCs (mEPSCs), an effect that became evident 1 h after antibody application. Interestingly, this effect is not isolated to AMPARs, as antibodies against NMDARs ( Dalmau et al, 2011 ), potassium channels ( Sun and Li, 2013 ; Sun et al, 2016 ), FGFR1 ( Opaliński et al, 2017 ), ErbB3 ( Belleudi et al, 2012 ), Human Respiratory Syncytial Virus Fusion Protein ( Leemans et al, 2017 ), and acetylcholine receptors ( Lee et al, 2014 ) also trigger a reduction of their respective target proteins. These studies suggest that antibodies against surface proteins induce internalization after the proteins are crosslinked if the samples are not maintained in the cold.…”
Section: Biological Limitations Of Ampar Mobilitymentioning
confidence: 99%
“…Other complement evasion mechanisms include the incorporation of host membrane complement regulatory proteins by budding enveloped virions, 88 molecular mimicry 89 or recruitment of such host regulatory factors, 87,90 and production of other complement‐disrupting factors such as complement‐cleaving enzymes, 91 and interference with C1q‐associated serine proteases 92 . Another mechanism of complement evasion, and evasion of antibody‐mediated effector function more generally, is antibody‐induced antigen internalization on virally infected host cells 93,94 . These pathogen evasion mechanisms, and others, have been extensively reviewed recently 95 .…”
Section: Role In Infectious Disease: From Elimination To Evasion To Ementioning
confidence: 99%